ENHANCING THE STUDENTS' WORD LEARNING WITH EXPLICIT INSTRUCTION OF SPECIFIC WORDS AT SMPN 3 PATTALLASSANG - Hanisa Masuku; Erwin Akib; Ariana (English Language Teaching Methodology, 2022)
The objective of this research was to find out how explicit instruction increased students' knowledge of certain words and to know out whether there was a significant increase in knowledge of words taught with explicit instructions at SMPN 3 Pattallassang.This research used the Pre-experimental Design as a research design that involves two types of instruments in data collection, namely pretest and posttest. The subject of this research was eighth grade students at SMPN 3 Pattallassang which consist of one class. The object of this research was the eighth grade students. The data was analyzed by significant differences on students' knowledge of specific words before after being taught with explicit instruction.The findings of this study concluded that the used of explicit instruction improved the vocabulary mastery of eighth grade students of SMPN 3 Pattallassang. This was evidenced by the average score of the test, vocabulary in terms of verbs in the pre-test was 54.56 and post-test was 80.32, and the improvement from pre-test to post-test was 47%, the average score of the test in terms of words objects in the pre-test was 52.08 and the post-test was 75.47, and the improvement from pre-test to post-test was 42%, the mean test score in terms of adjectives in pre-test was 56.08 and post-test was 82.64, and the improvement from pre-test to post-test was 48%, the average score students' vocabulary in the pre-test was 54.48 and after the post-test was 79.47 and the improvement from pre-test to post-test was 46%.